Epizootological Study and Molecular Diagnosis on Rift Valley Fever Disease In The Egyptian Border Governorates - G.Abdelwahab, Mohamed; El-Shourbgy, Atef M. A.; M.Moust, Abdelmoneim; Hassan, Sayed A. (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2018)
Rift valley fever (RVF) is a zoonotic disease which affects both humans and animals. It is caused by a Arbovirus which is maintained in nature through transmission between susceptible vertebrate hosts and blood sucking arthropods such as mosquitoes. In this study, an epidemiological investigation was carried out to evaluate the current situation in nine border Governorates of Egypt for Rift Valley Fever disease (RVF). Nine hundred thirty serum samples were collected randomly from Aswan, Red Sea, Alwadi El-Gdid, Marsa Matroh, North Sini, South Sini, Seuze, Ismailia and Port Said governorates. Samples were collected from different animal species such as cattle, camel, sheep and goat from May to October 2013. Serodiagnostic studies were done on serum samples by using commercial competitive ELISA for detection of IgM and IgG antibodies against Rift valley fever virus. 64 out of 930 samples in percentage of 9.3% were positive for detection of IgG antibodies against RVFV and all serum samples were negative for detection of IgM against RVFV. To confirm that the presence or absence of RVFV in the positive serum samples, RT-PCR using primers targeting the S segment was carried out. Sixty four positive serum samples and collected insects were subjected to rt-PCR to amplify 390 bp S segment of RVFV and the results were confirmed negative for all.